(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
The focus of this study is on the existence of three solutions to (p(·), q(·))-biharmonic operator with an s(x)-Hardy term under no-flux boundary conditions. Our method is based on the variational method and critical point results.